Gestión Financiera De La Asociación De “Madres Emprendedoras” “Amesepreve - Guaita Del Rosario, Andrea Katherine (2018)
In our country associations have been developed that promote employment, development and entrepreneurship in order to be sustainable the same as they can be independent in their economic growth. These groupings require management for the development of their daily activities in order to provide a good or service to the community and obtain the desired profitability that contributes to the increase of its capital. Associations grouped together and developing a popular and solidary economy have Strengthened self-employment, its sustainable development and its great economic contribution to the country. From the year 2009, the associations were increased with the help of the Institute National Popular and Solidarity Economy (IEPS), attached to the Ministry of Inclusion Economic and Social The financial management that is currently carried out within the associations can improve, since there is a certain degree of ignorance in the processes. In addition to, guidelines can be applied to obtain the required external financing and achieve their proposed objectives. The problem in the Association of Enterprising Mothers for the Provision of Clothing and Marketing Services for Clothing "Victoria y Paz "(AMESEPREVE), is the poor administration of financial resources and the ignorance of the processes to get the capital. These two factors lead to the association not being able to meet its goals raised and achieve the highest desired profitability. So, the purpose of this study case is to analyze such financial management and thus improve their profitability levels. research method proposed in this case is the deductive, since it is intended to reach to conclusions based on the information and data provided by the association.